Application of community law in the United Kingdom, 1994-1998 - Chalmers, Damian (2000)
Considers questions that have arisen about ratification of the Treaty on European Union and the Treaty of Amsterdam. Considers also, questions that have been provoked by the Court of Justice's 'constitutionalizing' case law about the status of EC law within the United Kingdom and the type of rights it generates. Focuses on various fields of EC law that have been applied in British case law.